Eksplorasi Endapan Hidrotermal di daerah Kasihan, Pacitan, Jawa Timur - Asrafil Asrafil; Arifudin Idrus; Djoko Wintolo (Pusat Survei Geologi, 2017)
This research aims to identify hydrothermal mineral deposits using geomagnetic methods. The geomagnetic method used to obtain anomaly of magnetic field intensity contrast. Furthermore, there is also been conducted taking and analysis samples of rock using petrography, ore microscopic and XRD. It is done to obtain mineralogical characteristics of hydrothermal mineral deposits that becoming the exploration target. The results showed that hydrothermal mineral deposits in research area was characterized by hydrothermal alteration of argillic (kaoline-illite), propylitic (calcite-chlorite) and skarn (quatrz-calcite-pyroxine/ clinopyroxine). Ore minerals are present of sulphide minerals such as pyrite, chalcopyrite, sphalerite, covelit and oxide minerals such as hematite abundance. The existence of hydrothermal mineral deposits are associated with skarn type deposit. Zones of mineral deposits of metallic ores are characterized by a significant contrast magnetic anomalies with high magnetic field intensity higher than 110,31 nT on the total magnetic intensity anomaly and higher than 11,09 nT on the residual magnetic intensity anomaly, as the response from the presence of metal in the ore mineral enrichment of rock material.keywords : hydrothermal minerals, magnetic field anomaly, petrography, ore microscopic, XRD skarn, Kasihan